دور المناشط الجامعية في تعزيز الوحدة الوطنية من وجهة نظر طلبة جامعة الملك خالد بالمملكة العربية السعودية - البحيري، محمد بن حامد محمد (جامعة السودان للعلوم والتكنولوجيا - عمادة البحث العلمى, 2018)
This study aims to identify the role of university activities in promoting national unity from the perspective of a sample of King Khalid University students, and their proposed vision to strengthen the national unity through these activities. In order to achieve the research aims, the researcher used descriptive methods by using a questionnaire consisted of (25) items and open ended questions about the suggested activates the research sample wants to add. A sample of (162) students from different colleges was surveyed. The results showed that the university activities are effective in promoting national unity. There are no differences between the sample in the role of university activities in promoting national unity due to the sex factor. There are no differences among the sample in the role of university activities in promoting national unity due to the specialization factor. The activities of great importance correspond to the wishes of the students to satisfy their psychological and cognitive needs and at the same time promote the values of national unity and belonging.
يعني هذا البحث إلى الكشف عن دور المناشط الجامعية في تعزيز الوحدة الوطنية؛ وذلك من وجهة نظر عينة من طلبة جامعة الملك خالد، كما يهتم بمعرفة ما يقترحونه من أفكار لتعزيز الوحدة الوطنية من خلال تلك المناشط، ولتحقيق أهداف البحث استخدم الباحث المنهج الوصفي، وأعدت استبانة تشتمل على (25) عبارة، بالإضافة إلى سؤال مفتوح عن التصور المقترح منهم لتعزيز الوحدة الوطنية من خلال المناشط الطلابية، وقد تم استطلاع آراء عينة مكونة من (162) طالباً وطالبة من كليات مختلفة، وقد أظهرت النتائج أن المناشط الجامعة فعالة في تعزيز الوحدة الوطنية ولا توجد فروق بين أفراد العينة في دور المناشط الجامعية في تعزيز الوحدة الوطنية تعزى إلى عاملي الجنس والتخصص وأن العناية بالمناشط لها أهمية كبرى تتوافق مع رغبات الطلاب لإشباع حاجاتهم النفسية والمعرفية وتعزز في الوقت نفسه قيم الوحدة الوطنية والإنتماء.
Keywords: طلبة الجامعة -- المناشط الجامعية -- الأنشطة الطلابية -- الوحدة الوطنية -- جامعة الملك خالد